Divan Şiiri Gazellerinde Tasvir ve Tahkiye - Karaköse, Saadet (Gökkubbe, 2004)
Gerçekleri yansıtmamakla eleştirilen Divan şiiri, aslında devrinin bütün yaşantısını yaşam felsefesiyle birlikte yansıtmaktadır. Konu bütünlüğü olan yek-ahenk gazeller, bütün olarak bakıldığında tasvirler içine yerleştirilmiş olaylarla, birer hikaye anlatabilmektedir. Bugün, hikayeyi oluşturan zaman, mekan, şahıs ve olay etmenleri, tek bir olaya kadar indirgenmiştir. "Kısa hikaye" denilen anlatım biçimi, bir beyit veya bir mısrada bile karşımıza çıkabilir. Divan şiirine bakıldığında anlatılan hikaye, klasik hikaye biçimindedir. Gazelierin çoğu, dramatik hikaye türündedir. Classic Turkish Poetry, called "gazelle", has been critized to be having some imaginary and also not showing realities which connect its social groups. We have seen them to be an ordinary poets for hundreds of years. We didn't noticed them whether to make an allusion to our minds. But, we havs seen some social realities at gazelles if we notice them having respect of narration. Today story, especially short story, has been a lot of many kinds of literature. Because, a story is chain of events and it can be as short as a sentence. The gazelle tells us some descriptions in which has events. Events have been related to each other and it ends an event which involved interrogation. When events deal with for a story, not only a gazelle but also a couplet of gazelle has included a short story. Story is classifıed two manner: A. As to substance : 1.story of fact, 2. story of fancy. B. As to form : 1.stories told historically, 2. stories told dramatically, 3. stories told didactically . According to this classify the gazelle has stated story of fact and dramatic story. The gazelle include dramatic events. So it can be examined to be a story as much as it examined an estetic poet.
The Description and Narration in the Gazels
Keywords: Türk Edebiyatı; Gazel; Drama; Tasvir; Tahkiye; Turkish Literature; Gazelles; Drama; Description; Narration